Fundamentals of conservation biology - Hunter, Malcolm L. (Blackwell Science, 2002)
The conservation of biodiversity is one of the most important issues facing ecologists today. In this update of the highly successful first edition, Malcolm Hunter introduces students and professionals to the fascinating and important field of conservation biology, the applied science dealing with the maintenance of the earth's biological diversity. Fundamentals of Conservation Biology 2e focuses on what can be done to maintain biodiversity through management of ecosystems and populations. Starting with a succinct look at what conservation and biodiversity really mean and progressing to more complex topics such as mass extinctions, habitat degradation and over exploitation, Hunter creates a context in which the principles of conservation biology can be readily understood. discussions of the social, political and economic aspects of conservation biology issues are interwoven throughout the text and addressed independently in their own chapters. The new edition has been thoroughly revised with hundreds of new references and web links to many of the organisations involved in conservation biology.